Pengaruh Insentif Pajak, Literasi Keuangan Terhadap Keberlangsungan Usaha Pelaku UMKM di Parungpanjang - Nur Khalifah; Luh Nadi (eCo-Fin, 2024)
The rapid growth of MSME in Parungpanjang region is not accompanied by awareness of paying taxes and having an understanding of financial literacy, it will be an effect on their business development. The purpose of this study is determining the effect of Tax Incentives, Financial Literacy on Business Sustainability of MSME in Parungpanjang. This study uses all MSME who were registered as taxpayers, sampling method using saturated contained in Non-Probability Sampling. This saturated sampling technique chosen because the number of MSME actors registered as taxpayers in Parungpanjang limited, therefore sample study 64 of MSME. Method analysis is processed using linear regression. The results of the simultaneous test of tax incentives and financial literacy have a significant effect on business continuity. Tax incentives has an effect business continuity. Financial literacy also has an effect on business continuity, this research proves that the level of education plays an important role because it increases financial literacy and understanding of finances in running a business. Apart from that, tax payments by MSME can encourage business continuity with additional capital provided by assistance from the government.